Can Tumor Necrosis Factor-α and Interleukin-6 Be Used as Prognostic Markers of Infection following Ureteroscopic Lithotripsy?. (30th January 2014) - Bantis, Athanasios; Tsakaldimis, Georgios; Zissimopoulos, Athanasios; Giannakopoulos, Stilianos; Kalaitzis, Christos; Pitiakoudis, Michail; Polichronidis, Alexandros; Touloupidis, Stavros
Abstract : Introduction . Ureteroscopic lithotripsy (URS) although highly effective for the treatment of ureteral stones is associated with certain complications, the more common of which are postoperative fever and infection. In the present study we aimed to evaluate the levels of serum cytokines in patients undergoing ureteroscopic lithotripsy and investigate any possible correlation between levels of cytokines and infectious complications after URS. Materials and Methods . Thirty patients (19 males, 11 females), with a mean age of 47 (range: 26–68) that underwent URS lithotripsy for ureteral stones, and 10 healthy volunteers serving as the control group were enrolled in this study. Serum samples for TNF- α and IL-6 were obtained before surgical intervention and after 1, 24, and 48 hours and 2, 24, and 48 hours, respectively. The preoperative and postoperative levels were compared and correlated with the possible complications after URS. Results . Serum TNF- α levels were statistically significant, increased 1 hour (P = 0.0083 ) and 48 hours (P < 0.001 ) after operation. IL-6 levels were found statistically significant, elevated after 2 and 24 hours from the URS (P < 0.001 ). In 2 patients we observed postoperative fever (>38.5°C). These two patients had high preoperative values of TNF- α and IL-6 ( 30 and 50 pg/mL, resp.) and these values increased postoperatively. Conclusion . High preoperative levels of serum TNF- α and IL-6 may indicate a predisposition for postoperative inflammation and infection following URS lithotripsy.